2022
DOI: 10.3389/fgene.2022.942785
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value and immune landscape of a cuproptosis-related lncRNA signature in head and neck squamous cell carcinoma

Abstract: Background: Cuproptosis has been recognized as a novel regulatory cell death, which has been confirmed to promote the occurrence and development of tumors. However, whether cuproptosis-related lncRNA has an impact on the prognosis of squamous cell carcinoma of the head and neck (HNSCC) is still unclear.Methods: In total, 501 HNSCC tumor samples and 44 normal were downloaded from the TCGA database. Cuproptosis-related lncRNAs were obtained by co-expressed analysis. We got prognostic lncRNA that was associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 74 publications
2
12
0
Order By: Relevance
“…We observed that cuproptosis was closely associated with KLF3‐AS1and LINC01063. CDKN2A‐DT and AC090587.1 had been reported could act as cuproptosis‐related biomarkers in HNSCC, 40 , 41 which was consistent with our findings. However, compare with the signatures with eight or more cuproptosis‐related lncRNAs, our algorithms with six cuproptosis‐related lncRNAs were simpler and easier for verification in the future applications.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We observed that cuproptosis was closely associated with KLF3‐AS1and LINC01063. CDKN2A‐DT and AC090587.1 had been reported could act as cuproptosis‐related biomarkers in HNSCC, 40 , 41 which was consistent with our findings. However, compare with the signatures with eight or more cuproptosis‐related lncRNAs, our algorithms with six cuproptosis‐related lncRNAs were simpler and easier for verification in the future applications.…”
Section: Discussionsupporting
confidence: 93%
“…32 Mao et al 33 reported that KLF3-AS1 present in the exosomes secreted from human mesenchymal stem cells could help reduce the extent of pyroptosis in cardiomyocytes and improve myocardial infarction by exploiting the miR-138-5p/Sirt1 axis. LINC01063 was associated with ferroptosis [34][35][36] and autophagy [37][38][39] CDKN2A-DT and AC090587.1 had been reported could act as cuproptosis-related biomarkers in HNSCC, 40,41 which was consistent with our findings. However, compare with the signatures with eight or more cuproptosis-related lncRNAs, our algorithms with six cuproptosis-related lncRNAs were simpler and easier for verification in the future applications.…”
Section: Discussionsupporting
confidence: 92%
“…We downloaded the small molecule structures from Drug Bank ( http://www.drugbank.com/ ) in SDF format ( Luo et al, 2022b ). In RDKit, the Experimental-Torsion Basic Knowledge Distance Geometry (ETKDG) algorithm was used to generate 3D conformations based on the modified distance geometry algorithm, while the MMFF94 stand was used to optimize small molecule structure and energy using the MMFFOptimize Molecule module ( Li et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…In melanoma, lung cancer, and renal clear cell carcinoma, cuproptosis-related genes have been studied. In recent studies, researchers examined ten cuproptosis-related lncRNAs associated with immune function and prognosis in HNSCC ( Li et al, 2022 ). However, the functions and mechanisms of action of cuproptosis-related genes in HNSCC warrant further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence also suggests crosstalk between curoprotosis and the tumor immune microenvironment (TME) ( Lv et al, 2022 )- ( Li et al, 2022a ). The tumor microenvironment plays a crucial role in cancer development and clinical outcomes ( Wu and Dai, 2017 ).…”
Section: Introductionmentioning
confidence: 99%